Therapeutic potential of transdermal glyceryl trinitrate in the management of acute stroke - Appleton, Jason P.; Sprigg, Nikola; Bath, Philip M.W. (Adis, 2016)
The nitric oxide donor, glyceryl trinitrate (GTN), is a candidate treatment for the management of acute stroke with haemodynamic and potential reperfusion and neuroprotective effects. When administered as a transdermal patch during the acute and subacute phases after stroke, GTN was safe, lowered blood pressure, maintained cerebral blood flow, and did not induce cerebral steal or alter functional outcome. However, when given within 6 h of stroke onset, GTN reduced death and dependency (odds ratio 0.52; 95% confidence interval 0.34–0.78), death, disability, cognitive impairment and mood disturbance, and improved quality of life (data from two trials, n = 312). In a pooled analysis of four studies (n = 186), GTN reduced between-visit systolic blood pressure variability over days 1–7 compared with no GTN (mean difference -2.09; 95% confidence interval -3.83 to -0.35; p = 0.019). The efficacy of GTN given in the ultra-acute/pre-hospital setting is currently being assessed and, if found to be beneficial, the implications for hyperacute stroke practice are significant. Here, we discuss the evidence to date, potential mechanisms of action and future possibilities, including unanswered questions, for the therapeutic potential of GTN in acute stroke.